Safety and efficacy of osimertinib rechallenge or continuation after pneumonitis: A multicentre retrospective cohort study. (January 2023) - Imaji, Mihoko; Fujimoto, Daichi; Sato, Yuki; Sakata, Yoshihiko; Oya, Yuko; Tamiya, Motohiro; Suzuki, Hidekazu; Ikeda, Hideki; Kijima, Takashi; Matsumoto, Hirotaka; Kanazu, Masaki; Hino, Aoi; et al.
Abstract: Introduction: Although osimertinib is a standard first-line treatment for patients with advanced-stage non-small cell lung cancer (NSCLC) with epidermal growth factor receptor ( EGFR ) mutations, the incidence rate of pneumonitis associated with osimertinib is high. However, there are few reports about the safety and efficacy of osimertinib rechallenge after the development of pneumonitis. Methods: We conducted a retrospective multicentre cohort study of consecutive patients who developed pneumonitis associated with osimertinib as a first-line and received osimertinib rechallenge. The primary outcome was the incidence rate of any grade pneumonitis after osimertinib rechallenge. The secondary outcome was treatment efficacy in patients after osimertinib rechallenge. Results: In total, 33 patients who received osimertinib rechallenge were included. Of them, 26 patients had grade 1, 6 patients had grade 2, and 1 patient had grade 3 initial pneumonitis. The median follow-up period after the osimertinib rechallenge was 16.9 months (interquartile range, 11.1–21.3 months). After the start of osimertinib rechallenge, five patients (15%) experienced mild relapsed pneumonitis. Three of the five patients had similar imaging patterns for initial and relapsed pneumonitis. No significant differences in characteristics were observed between patients with and without relapsed pneumonitis. The median progression-free survival after osimertinib rechallenge was not achieved (95% confidence interval: 10.3 months – not reached). Conclusion: Osimertinib rechallenge was feasible and effective for patients who developed initial pneumonitis associated with first-line osimertinib therapy. Osimertinib might be considered a treatment option even after the development of mild initial pneumonitis. Highlights: Large study of 33 patients with osimertinib continuation or re-administration after pneumonitis. The incidence rate of relapsed pneumonitis was 15%, and all were mild. Osimertinib may be safely and effectively administered after control of initial pneumonitis.